Integrating Qur’anic Thematic Interpretation with Empirical Observation: An Analysis of Students’ Islamic Character at SMP Negeri 1 Kalijati - Salsabila Mustopa; Tryana Hafilda; Reza Fahlefi; Hafid Muslih; Cecep Anwar; Muhammad Hilmi Ramadhan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This study aims to analyze students’ Islamic character from the perspective of thematic interpretation of the Qur’an through direct observation at SMP Negeri 1 Kalijati, Subang, Indonesia. The research focused on key character indicators, such as honesty, discipline, respect, and cooperation, which were then linked to the moral values contained in Qur’anic verses related to moral education. This study employed a descriptive qualitative approach, utilizing Miles & Huberman’s interactive data model, supported by descriptive quantitative data and thematic interpretation analysis (al-tafsīr al-mawḍū’ī). The data were analyzed thematically to identify the relationship between student behavior in the school context and the principles of Islamic character education, as interpreted in the Qur’an. The results showed that most students displayed positive behavior in accordance with Islamic teachings, although several challenges remained in the aspects of consistency and internalization of values. However, previous studies tend to separate empirical character assessment from Qur’anic exegesis, leaving a methodological gap in integrating observed behavior with thematic Qur’anic interpretation. This study emphasizes the importance of strengthening character education based on Quranic values in the school environment to shape a generation with noble morals that are relevant to their daily social context.